Prevalence nutritional disorders among patients hospitalised for stroke and discopathy in the neurology department - Sierżantowicz, Regina; Jakimiuk, Lucyna; Lewko, Jolanta; Stępień, Renata; Trochimowicz, Lech; Zimnoch, Ryszard (Medical Studies/Studia Medyczne, 2015)
Introduction: Nutritional disorders pose a huge health problem worldwide. In Poland, symptoms of malnutrition are found on admission to hospital in approximately 30% of patients. Among neurological disorders that predispose to malnutrition, brain injuries are the most frequent. The disease leads to difficulties with self-care, disorientation, reduced intellectual capacity, and dysphagia. Acute spinal pain syndromes affect weight loss because of persistent severe pain, and frequent dizziness and headaches accompanying cervical discopathy. Aim of the research: To assess the degree of malnutrition in patients with stroke and discopathy hospitalised in the neurology ward. Material and methods : The study group consisted of 141 patients, including 90 with stroke and 51 with discopathy, hospitalised in the neurology ward. Research material was collected based on medical records and a proprietary questionnaire. Body mass index (BMI) was calculated and assessed for each patient on admission and after hospitalisation. Results and conclusions: The study sample consisted of a similar group of women (49%) and men (51%) aged from 30 to over 70 years. Ischaemic stroke was diagnosed more often in women (66.2%), whereas discopathy was more common in men (43.4%). The differences in BMI present on admission and after hospitalisation in men and women indicated a falling tendency. A slightly greater drop in BMI was found in women after hospital stay (from 24.1 to 23.3 kg/m 2 ). The lowest BMI on admission was observed in students and pensioners. Long-term hospitalisation significantly affected weight reduction – the longer the patients were hospitalised, the lower their BMI was. Preliminary assessment of the nutrition status on admission to a hospital ward and customising individual diets may help reduce the effects of malnutrition.